Compliment responses across gender in Philippine context - Morales, Rodrigo Concepcion (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
A number of researches on compliments and compliment responses (CRs) have been done from cross-cultural perspectives; however, few attempts have been made to conduct contrastive studies across gender. This study analyzed the results from 15 male and 15 female advanced L2 learners in Parañaque Science High School to determine what CRs strategies and types of compliments they employed. From the data collected, results revealed that the male and female participants opted to follow the trend from the previous studies: Accept, Reject, and Evade pattern. Both groups preferred Accept the most, and Reject the least. In addition, two explicit types of CRs strategies were evidently preferred by both groups: the Appreciation Token and Return Compliment. On the one hand, male participants preferred to use implicit CRS strategy of Informative Comment; but on the other hand, female participants opted to employ implicit CRS strategy of Shift Credit. The linguistic manipulations of CRs shown in this study indicate that no universal model of CRs would work because different genders have different sets of protocols, thereby preventing any valid generalization. Several pedagogical implications were provided for future instruction in teaching ESL.